Comparative study of the osteogenic ability of four different ceramic constructs in an ectopic large animal model. (20th June 2013) - Viateau, Véronique; Manassero, Mathieu; Sensébé, Luc; Langonné, Alain; Marchat, David; Logeart‐Avramoglou, Delphine; Petite, Hervé; Bensidhoum, Morad
Abstract: Tissue‐engineered constructs combining bone marrow mesenchymal stem cells with biodegradable osteoconductive scaffolds are very promising for repairing large segmental bone defects. Synchronizing and controlling the balance between scaffold‐material resorption and new bone tissue formation are crucial aspects for the success of bone tissue engineering. The purpose of the present study was to determine, and compare, the osteogenic potential of ceramic scaffolds with different resorbability. Four clinically relevant granular biomaterial scaffolds (specifically, Porites coral, Acropora coral, beta‐tricalcium phosphate and banked bone) with or without autologous bone marrow stromal cells were implanted in the ectopic, subcutaneous‐pouch sheep model. Scaffold material resorption and new bone formation were assessed eight weeks after implantation. New bone formation was only detected when the biomaterial constructs tested contained MSCs. New bone formation was higher in the Porites coral and Acropora coral than in either the beta‐tricalcium phosphate or the banked bone constructs; furthermore, there was a direct correlation between scaffold resorption and bone formation. The results of the present study provide evidence that, among the biomaterials tested, coral scaffolds containing MSCs promoted the best new bone formation in the present study. Copyright © 2013 John Wiley & Sons, Ltd.